Hamlet, lesson 1 the age of Elizabeth (Illinois, Chicago Britannica Encyclopedia Britannica Educational Corporation)
Maynard Mack introduces us to the classes and customs of the Elizabethan Age. He also discusses the Elizabethan theater and its audience.
Summary from back of the container.
Title from container.
Stratford Shakepearean director of dramatic sequence, Douglas Campbell; Encyclopedia Britannica film director, John Barnes; assistant director C. Walter Hodges; cameraman, Michael Livestry; editors, Robert Johnson & Fred Laser; costume designer, Desmond Heeley; property master, Brian Jackson; Massachusetts Council For Humanities executive director, Floyd Rinner; associate director, Angela McDermott; director for film, Michael Bohmer; production manager, Curtis Davis; operation manager, William Hall.
Peter Donat, Douglas Camphill, Tony Van Bridor, Donald Davis, William Needles.
VCD, region 1, anamorphic widescreen (1.85:1).
English.
Keywords: William Shakespeare -- playwright -- 1564-1616.; Elizabeth I -- Queen, daughter of King Henry VIII, King of England -- 1533-1603.; Sir Frances Drake, Elizabethan Naval Commander -- 1540-1596).; Hamlet -- Play -- Tragedy; Elizabethan Age -- Classes and customs; Elizabethan Theater; Feature films; Historical films; Biographical films